PENYELESAIAN DAN PENANGGULANGAN KORBAN KEKERASAN DALAM RUMAH TANGGA MELALUI LEMBAGA ADAT NAGARI DI SUMATERA BARAT - Hasneni Hasneni (Universitas Islam Negeri Imam Bonjol Padang, 2014)
The high rate of domestic violence is influenced by the lack of institutions in completing and anticipating it, besides the tendency of indigenious culture which consider it as a common problem. Nevertheless, in West Sumatra, the strengthening of local institutions has been one of the assets that can prevent the occurrence of these domestic violences. This study found that the existence of economic institutions, the strengthening of women’s institutions and women's economic empowerment in the village can reduce the occurrence of such violence. This research was conducted in some progressing-villages in West Sumatra: Simarasok Baso in Agam regency and Rao-Rao Sungai Tarab in Tanah Datar regency.Keywords: Domestic violence and Institutional indigenous villagesCopyright © 2014 by Kafa`ah All right reservedDOI : 10.15548/jk.v4i1.87